DIPLOMASI SPIRITUAL KULTURAL DALAM PENCEGAHAN PEMBAYARAN DIYAT SEBAGAI UPAYA PERLINDUNGAN HUKUM WNI DI LUAR NEGERI YANG MENERAPKAN SYARIAT - Tamami, Kholidah (An Nawawi, 2021)
The program to protect Indonesian citizens (WNI) abroad is one of the agendas for the Nawacita program of the Joko Widodo-Jusuf Kalla administration. Some of the protection efforts in the Middle East, the government often collides with qishas which is part of Islamic law in the country. The death sentence that befell the Indonesian citizen occurred because the victim's family did not forgive the Indonesian citizen who was suspected of being guilty, even the power of the king could not intervene in this matter. The presence of the state in the form of providing assistance from lawyers, involving local figures is a way of diplomacy that can relieve Indonesian citizens who are sentenced to prison in that country. Throughout 2015, the Ministry of Foreign Affairs through Indonesian Representatives in several countries has succeeded in freeing 48 Indonesian citizens from the threat of the death penalty. This study uses a descriptive qualitative method of analysis by collecting observation data, interviews, document collection and recording.